Use of Learning Cooperative Integrated Reading and Composition to the Learning Achievement Indonesian Languange Correspondence in Study Programs of Office Administration - Brillian Rosy (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2018)
This research aims to determine the effect of the CIRC learning model on learning achievement in the Indonesian Language Correspondence course material for writing official letters. This type of research is experimental form of non equivalent control group design. The subject of the study was all students of UNESA 2016 Office Administration Education Study Program totaling 88 students in which the experimental class was determined as class A and the control class was class B. In the learning control class, it was used the direct instruction model, while the experimental class was treated using the CIRC model. The research uses various instrument tests such as pre-test, post-test, and assignments to make official letters. The results showed that there were significant differences when comparing the average score of the control class with the experimental class, namely the cooperative reading and composition cooperative learning model had a significant effect on students’ achievement.